A circadian sleep disorder reveals complexity in the clock - Mignot, Emmanuel (2007)
Circadian rhythms are established by transcription of clock genes and autoregulatory transcriptional feedback loops. In this issue, Xu et al. (2007), characterize mice expressing a human Per2 mutation identified in patients with Familial Advanced Sleep Phase Syndrome. Their results reveal that PER2 phosphorylation— by CK1δ and other kinases—is surprisingly complex and has opposite effects on PER2 levels and period length.